The effectiveness of the means to implement recreational sports activity in reducing in people with myopathy - bouras , mohamed; Bakhoch, hamida (sports creativity, 2025)
This study aims to try to highlight the effectiveness of the means of implementing recreational sporting activities and its contribution to reducing the depression status in the category of patients with myopathy, as this study relied on the descriptive analytical approach as being appropriate to the quality of this study, as the research sample consisted of 30 patients with myopathy They were randomly chosen from the Challenge Association in the municipality of Tazmal, Bejaia, and the depression scale was applied to them as a statistical tool. The researcher reached the following results: - - The means to implement recreational sports activities are effective and have a great role in reducing depression in the muscular people - - There was a positive interaction for this category during the implementation of the recreational sporting activities